Середньовічні матеріали із розкопок Білгород-Дністровської експедиції 1946—1947, 1949—1950 рр. - Карашевич, І.В. (Археологія і давня історія України, 2010)
До наукового обігу вводиться середньовічний комплекс матеріалів із розкопок Тіри 1946—47, 1949—
1950 рр. під керівництвом Л.Д. Дмитрова, що зберігаються у Наукових фондах ІА НАН України. Археологические исследования 1946—1947, 1949—
1950 гг. Аккерманской крепости Белгород-Днестровской (Измаильской) экспедицией внесли некоторые
изменения в старое представление об исторической
топографии, планировке города, жизни и быта, занятий жителей не только античной Тиры, но так же средневекового Белгорода — Четати Албе, Аккермана. На основании вещественного материала, хранящегося в
Научных фондах Института археологии НАН Украины средневековые материалы из верхних слоев гласиса
крепости относятся к XIII—XVII векам. Основная масса находок датируется XIII веком, а именно — золотоордынским периодом. Archaeological researches 1946—1947, 1949—1950 of
the Akkermansky fortress Belgorod-Dnestrovskoj (Izmailsky)
expedition have made some changes to old representation
about historical topography, a lay-out of a city, a
life and a life, employment of inhabitants not only antique
Shooting galleries, but as medieval Belgorod — Chetaty
Albe, Akkermana. On the basis of a material of Institute of
archeology National academy of sciences of Ukraine stored
in Scientific funds medieval materials from the top layers
glasis fortresses concern to XIII — to XVII centuries.
The great bulk of finds is dated XIII century, namely the
Golden Horde period.